Small-angle neutron scattering in Invar Fe-Ni-C alloys in magnetic field - Nadutov, V.M.; Garamus, V.M.; Willumeit, R.; Semenov, D.V. (Functional Materials, 2004)
The small-angle neutron scattering (SANS) in Invar Fe-Ni and Fe-Ni-C alloys was studied using polarized neutrons. The measurements were carried out without and with applied magnetic field of 2.5 T at the sample perpendicular to the neutron beam. The nonlinear SANS curves were obtained within the range of scattering vector q = 0.0060.025 A⁻¹ and analyzed using power law function. The considerable magnetic contribution to neutron scattering has been demonstrated. The size of aggregates has been estimated using the Indirect Fourier Transformation method. Исследовано малоугловое рассеяние нейтронов (МУРН) в инварных Fe-Ni и Fe-Ni-C сплавах с использованием поляризованных нейтронов. Измерения проведены без магнитного поля и с наложенным к образцу магнитным полем 2,5 Т, перпендикулярным направлению пучка нейтронов. Получено нелинейную кривую МУРН в интервале векторов рассеяния q = 0.006-0.025 A⁻¹, проанализировано с использованием степенной функции. Продемонстрирован существенный магнитный вклад в рассеяние нейтронов. С использованием косвенного фурье-преобразования оценены размеры неоднородностей. Досліджено малокутове розсіяння нєйтронів (МКРН) в інварних Fe-Ni та Fe-Ni-C сплавах з застосуванням поляризованих нейтронів. Вимірювання проведено без магнітного поля та з прикладеним до зразка магнітним полем 2,5 Т перпендикулярним до пучка нейтронів. Отримано нелінійну криву МКРН в інтервалі векторів розсіяння q = 0.006-0.025 A-1 і проаналізовано з використанням степеневої функції. Продемонстровано суттєвий магнітний внесок у розсіяння нейтронів. З використанням непрямого фур’є-перетворення, оцінено розмір неоднородностей.